Prioritizing and implementing HPV vaccination quality improvement programs in healthcare systems: the perspective of quality improvement leaders - Brigid K. Grabert; Jennifer Heisler-MacKinnon; Amy Liu; Marjorie A. Margolis; Elizabeth D. Cox; Melissa B. Gilkey (Taylor & Francis Group, 2021)
Human papillomavirus (HPV) vaccination could prevent most of the ~34,000 HPV-attributable cancers diagnosed annually in the US, but uptake remains suboptimal. Healthcare systems are key partners in implementing HPV vaccination quality improvement (QI) programs. To inform future system-level HPV vaccine initiatives, we sought to understand HPV vaccine QI from the perspective of QI program leaders in healthcare systems. We conducted telephone interviews with a multi-state sample of 17 QI leaders in 15 systems. We analyzed data qualitatively via thematic analysis to describe QI leaders' perspectives on prioritizing and implementing HPV vaccine QI. All QI leaders endorsed HPV vaccination as beneficial, and some had already prioritized increasing uptake to improve adolescent health and meet payor reimbursement standards. Those not prioritizing HPV vaccination cited concerns including the relatively small size of adolescent patient populations, lack of buy-in among providers, and the need to focus on health services perceived as more profitable or urgent. When implementing HPV vaccine QI programs, QI leaders reported key barriers to be the lack of robust data systems and acceptable QI metrics, limited time, and pressures of a fee-for-service clinical environment. Facilitators included automation and standardization in QI efforts and passionate vaccine champions. Almost all QI leaders reported future plans to implement HPV vaccine QI projects. Findings suggest that many healthcare systems are motivated to improve HPV vaccination. However, resistance to guideline-consistent quality metrics, the narrow target of one vaccine in the adolescent patient population, payment structures, and constrained time of providers are key barriers to practice improvements.